2020
DOI: 10.2147/dddt.s230749
|View full text |Cite
|
Sign up to set email alerts
|

<p>Astaxanthin in Liver Health and Disease: A Potential Therapeutic Agent</p>

Abstract: Astaxanthin is a carotenoid derived from oxygen-containing non-vitamin A sources and is mainly obtained from marine organisms. Studies have demonstrated that astaxanthin is a natural antioxidant product and it is widely used in the fields of medicine, health-care products and cosmetics. Studies have shown that astaxanthin has important preventive and therapeutic effects on liver fibrosis, non-alcoholic fatty liver, liver cancer, drug and ischemia-induced liver injury, and its mechanism is related to antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 89 publications
2
29
0
Order By: Relevance
“…In terms of burn injury, we observed that ATX exerted a protective effect against burn-induced early AKI by ameliorating oxidative damage and downregulating mitochondria-related apoptosis via the PI3K/Akt/Bad pathway 7 . Combined with similar reports of its effects on oxidative damage and inflammation in other organ injuries, ATX seems to be a promising and nontoxic therapeutic reagent to prevent early AKI after burn injury 20 , 21 .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In terms of burn injury, we observed that ATX exerted a protective effect against burn-induced early AKI by ameliorating oxidative damage and downregulating mitochondria-related apoptosis via the PI3K/Akt/Bad pathway 7 . Combined with similar reports of its effects on oxidative damage and inflammation in other organ injuries, ATX seems to be a promising and nontoxic therapeutic reagent to prevent early AKI after burn injury 20 , 21 .…”
Section: Introductionmentioning
confidence: 68%
“…Astaxanthin (ATX) is a natural and strong antioxidant that can be extracted from multiple crustaceans 32 . ATX is considered to be a safe and hopeful therapeutic agent in several diseases, as well as a safe feed additive and dietary supplement 21 , 33 35 . Our previous study primarily demonstrated the protective value of ATX in burn-induced early AKI, and the mechanism of action was found to be related to its ability to attenuate oxidative stress and secondary renal cell apoptosis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, we need to explore the mechanisms of fenofibrate on how to attenuate the injury of IR. PPAR- α is a key transcription factor that mediates the nucleus–mitochondrial interactions to regulate inflammation, lipid metabolism, and mitochondrial functions in various tissues and cells, and it has become a main target in NFALD [ 36 , 37 ]. PPAR- α activation increases the expression of sirtuin-1 (SIRT1), which inhibits NF- κ B, depending on the AMPK pathway and thus reducing inflammation [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with β-carotene and vitamin E, AST has 10-fold and 100fold stronger antioxidant capacity, respectively (Li et al, 2020). In different experimental models, AST has a preventive effect on heart, kidney, lungs, and nerve injury through reducing oxidative stress in the organism (Ni et al, 2018;Xu et al, 2019;Yamagishi & Aihara, 2014).…”
Section: Introductionmentioning
confidence: 99%